The impact of head teacher praise and criticism on adolescent non-cognitive skills: Evidence from China - Ye, Xiaomei; Wang, Qiran; Pan, Yiming (Frontiers in Psychology, 2023)
Although many studies have confirmed the importance of teacher feedback, the association of head teacher praise and criticism with adolescents’ non-cognitive skills still needs more profound and extensive research. Based on CEPS data, this paper used panel regression and PSM-DID methods to analyze the impact of head teacher feedback on adolescent non-cognitive skills measured by the big-five personality scale. It found that head teacher praise positively influenced adolescents’ extraversion, agreeableness, openness, and conscientiousness yet mitigated their neuroticism. Meanwhile, the effect of criticism from head teachers is bi-facial. It positively affected adolescents’ extraversion and openness but impaired their conscientiousness and neuroticism. We also found that the rural-urban gap in adolescents' extraversion, agreeableness, neuroticism, openness, and conscientiousness will narrow by 12.51%, 16.58%, 11.35%, 14.25%, and 24.29% if the headteacher praise of rural adolescent improves to the average of urban. This finding has significant implications for head teacher teaching and adolescent well-being.